Recent Trends in Nanomaterial-Based Biosensors for Point-of-Care Testing - Wang, Xu; Li, Feng; Guo, Yirong (Frontiers in Chemistry, 2020)
Nanobiotechnology, which integrates nanoscience with biology and medicine, has recently attracted great attention in the field of biological analysis. Nanomaterials such as gold nanoparticles, magnetic particles, carbon nanomaterials, quantum dots, and nanocomposites are increasingly utilized for point-of-care testing (POCT) to improve the sensitivity and simplify the detection procedure. They are employed either as supports for immobilizing biorecognition elements or as electroactive, magnetic or optical labels for signal transduction and amplification. In this commentary, we highlight recent POCT technologies employing these nanomaterials for the detection of biomarkers, including proteins, enzymes, nucleic acids, small molecules, cancer cells, and pathogens. Recent advances in lateral flow tests, printable electrochemical biosensors, and microfluidics-based devices are summarized. Existing challenges and future directions are also discussed.